Growth improvement of immature quinine by applying coffee husk compost and biofertilizer - Maxiselly, Yudithia; Sa'adah, Dinda Rachmatis; Ariyanti, Mira; Prayoga, Muhammad Khais; Khomaeni, Heri Syahrian (Universitas Padjadjaran, 2024)
The growth of immature Cinchona ledgeriana can be optimized by applying fertilizers to fill the nutritional needs of plants. Nutrients can be provided through the help of microorganisms derived from organic fertilizers and biofertilizers. This study aims to evaluate the effect of applying coffee husk compost and biofertilizer consortium on the growth of immature quinine plants. This research was conducted from November 2023 – January 2024 at Gambung Tea and Cinchona Research Center, Pasir Jambu District, Bandung Regency, West Java. The research used a randomized block design with four replications and six treatments, namely control (Urea 17 g.plant-1 + SP36 8 g.plant-1 + KCl 4 g.plant-1); solid coffee husk compost 3 kg.plant-1; liquid coffee husk compost 80 mL.L-1; biofertilizer 10 mL.L-1; solid coffee husk compost 3 kg.plants-1 + biofertilizer 10 mL.L-1; and liquid coffee husk compost 80 mL.L-1 + biofertilizer 10 mL.L-1. The results showed applying organic fertilizer from coffee husk waste and biofertilizer improved the growth of immature quinine plants. Combination of liquid organic fertilizer from coffee husk waste 80 mL.L-1 water + biofertilizer 10 mL.L-1 water produced a high increase in leaf area. Combination of solid organic fertilizer from coffee husk waste 3 kg. plants-1 + biofertilizer 10 mL.L-1 water showed the highest plant height increment. It implied the success of quinine improvement growth at the immature phase by applying coffee husk waste and biofertilizers.